O MOVER DO ESPÍRITO: RITUALIDADE, PERFORMANCE, SELF SAGRADO E COMMUNITAS NO MINISTÉRIO VERBO DA VIDA EM CAMPO GRANDE-MS - OCLÉCIO ALVES CABRAL FILHO (2022)
This research aims to describe and analyze “Culto de Mover”, a ritual manifestation of Verbo da Vida Church in Campo Grande (MS). I seek to understand how rite is done and mobilizes beliefs, behaviors and affections among Verbeans. It makes distinctions of identity and provokes complex operations in formation of Communitas, Sacred-Self and religious habitus. I carried out field work from to. I made dense description and reported of interlocutors in different phases and positions in community, diversity of gender, age and ecclesiastical positions. For theoretical analysis, I discuss Victor Turner and Thomas Csordas. Turner elaborates notions of Communitas, Liminality and Symbolic Poles, while Csordas brings notions of Sacred Self and Religious Habitus. In my final remarks, I conclude that “Culto de Mover” acts are privileged spaces for transformation and decanting of new interpretations on themes and discourses listed in theology of the Instituto Rhema Brasil, the educational arm of Verbo da Vida. Therefore, ritual provides a moment of Communitas, where rules and norms of social structure are partially suspended. They are later reabsorbed by structure to generate Verbean identity that is strongly linked to emic notions of Word of Faith and Prosperity.